2022
DOI: 10.3389/fcell.2022.1065702
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of the BCL-2 family protein BCL-RAMBO, which regulates apoptosis, mitochondrial fragmentation, and mitophagy

Abstract: Mitochondria play an essential role in the regulation of cellular stress responses, including cell death. Damaged mitochondria are removed by fission and fusion cycles and mitophagy, which counteract cell death. BCL-2 family proteins possess one to four BCL-2 homology domains and regulate apoptosis signaling at mitochondria. BCL-RAMBO, also known as BCL2-like 13 (BCL2L13), was initially identified as one of the BCL-2 family proteins inducing apoptosis. Mitophagy receptors recruit the ATG8 family proteins MAP1L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 203 publications
(298 reference statements)
0
2
0
Order By: Relevance
“…BCL2L13 (BCL2-like 13, BCL-RAMBO) is an atypical member of the BCL2 family that regulates apoptosis, mitochondrial fragmentation, and mitophagy [95]. ACE2 stimulates the induction of browning in white adipose tissue [96], while the expression of BCL2L13 increases during white adipose tissue browning [97].…”
Section: Genes/proteins Identified By 1-l Transcription Of C-(aa)n-n ...mentioning
confidence: 99%
“…BCL2L13 (BCL2-like 13, BCL-RAMBO) is an atypical member of the BCL2 family that regulates apoptosis, mitochondrial fragmentation, and mitophagy [95]. ACE2 stimulates the induction of browning in white adipose tissue [96], while the expression of BCL2L13 increases during white adipose tissue browning [97].…”
Section: Genes/proteins Identified By 1-l Transcription Of C-(aa)n-n ...mentioning
confidence: 99%
“…BCL-RAMBO, also known as BCL2-like 13, was initially discovered as a pro-apoptotic protein 15 . Many studies have demonstrated that BCL-RAMBO controls cell death, mitochondria fragmentation, and mitophagy 16 , 17 . BCL-RAMBO consists of an N-terminal BH domain, a No BH (BHNo) domain, a transmembrane (TM) domain, and a short cytoplasmic tail 15 .…”
Section: Introductionmentioning
confidence: 99%